Programma: 26 mei B Boy Extravaganza; 30 mei Prophets of Da City; 2 juni Yellowman; 3 juni Big Soul
Programma: 26 mei B Boy Extravaganza; 30 mei Prophets of Da City; 2 juni Yellowman; 3 juni Big Soul.